Synopsis: The role of the locations of public sector varietal development activities on agricultural productivity - Takeshima, Hiroyuki; Nasir, Abdullahi Mohammed (International Food Policy Research Institute, 2017)
Using panel data from farm households in northern Nigeria and spatial data on agroecological factors, this study shows that crop productivity and technical efficiency at farm household level is positively affected by the degree of similarity between the agroecological conditions of the locations of these households and where major crop breeding institutes are headquartered. Where improved varieties are developed affects crop productivity in different locations.